2022
DOI: 10.1088/1742-6596/2265/2/022003
|View full text |Cite
|
Sign up to set email alerts
|

A surrogate model of offshore wind farm annual energy production to support financial evaluation

Abstract: The preliminary financial evaluation of wind farm profitability requires fast analysis of energy production and costs while having very little specific information around the project. Early in the design process, the selection of specific wind turbines and the layout design may not yet be defined. Techno-economic and financial analysis models have been developed to use input from a small set of high-level project characteristics to estimate major cost elements and energy production for a wind farm to support q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…All the simulations were performed in PyWake [12,13] and TOPFARM [14], an open-source tool developed by DTU Wind and that has been used in previous works in the literature [15,16,17,18,19]. The case-study considered in this work is the Borselle wind farm, which has 74 wind turbines with 10MW each.…”
Section: Optimization and Case Studymentioning
confidence: 99%
“…All the simulations were performed in PyWake [12,13] and TOPFARM [14], an open-source tool developed by DTU Wind and that has been used in previous works in the literature [15,16,17,18,19]. The case-study considered in this work is the Borselle wind farm, which has 74 wind turbines with 10MW each.…”
Section: Optimization and Case Studymentioning
confidence: 99%
“…These wind farms are designed to optimize energy production while minimizing costs associated with installation, operation, and maintenance. [19]. Designing a wind farm presents several challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, unlike traditional wind farm layout optimization, Cazzaro et al solved the problem of selecting the shape and area of a wind farm from a larger area to maximize profitability, 21 that is, by taking macro, meso, and micro as three different scales and designing a heuristic evolutionary algorithm to choose the best shape of a wind farm for the above three scales. Other studies on offshore wind farms can be found in various studies 22,23 …”
Section: Introductionmentioning
confidence: 99%
“…Other studies on offshore wind farms can be found in various studies. 22,23 To reduce the investment cost, the optimization problem of offshore wind farm cable layout has received more attention from researchers. Early relevant studies focused on minimizing cable length and adopted the graph theory 24 or the classical evolutionary algorithm 25 to optimize cable length.…”
mentioning
confidence: 99%